ANALYSIS OF BIRD'S NEST BUSINESS TOWARDS INCREASING COMMUNITY INCOME IN PELIMBANGAN VILLAGE, CENGAL DISTRICT, OGAN KOMERING ILIR REGENCY, SOUTH SUMATERA PROVINCE - Helida, Asvic; Syahroni, S.P, M.Si, Sasua Hustati; Hariyansa, Hariyansa (Sylva Jurnal Ilmu-ilmu Kehutanan, 2024)
Indonesia is one of the countries that has abundant biological natural resources, South Sumatra is a province with a population that is very interested in the swallow's nest business, especially OganKomeringIlir Regency is one of the areas with a large population of swiftlets so many entrepreneurs build nest buildings swallow in the region. The purpose of this study was to find out how the economic level and the economic impact of the community's swallow's nest business in Pelimbangan Village. This research method uses qualitative research methods. In this study, the first data collection technique was used by questionnaire research and the second used the interview method. Based on the results of the research, the researchers concluded that the economic level of the people in Pelimbangan Village, the existence of swallow's nest business, increased the community's income, receipts in one month Rp. 6,444,142 as well as the economic impact of the community on the swallow's nest business in the village of Pelimbangan.